Load Time Optimization on React Website using Incremental Static Regeneration with NextJS - Gede Sudimahendra; Luh Arida Ayu Rahning Putri (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
There’s a lot of tools that can be used to build or develop a website. Starting from basic HTML CSS and JavaScript to the use of UI Framework such as React, Angular, Vue JS or Svelte But, the use of UI Framework doesn’t come with no cons. UI Framework like React, use virtual DOM, instead of modifying the DOM directly, so when the first time application load, the framework needs to load library to modify the virtual DOM, before the page can load. This can leads to slow first loading time. This paper research performance improvement when using ISR ( Incremental Static Regeneration ) in NextJS